A genome-wide cross-phenotype meta-analysis of the association of blood pressure with migraine - Yanjun Guo; Pamela M. Rist; Iyas Daghlas; Franco Giulianini; International Headache Genetics Consortium; 23andMe Research Team; Tobias Kurth; Daniel I. Chasman (NATURE PUBLISHING GROUP, 2022)
Blood pressure (BP) was inconsistently associated with migraine and the mechanisms of BP-lowering medications in migraine prophylaxis are unknown. Leveraging large-scale summary statistics for migraine (N-cases/N-controls = 59,674/316,078) and BP (N = 757,601), we find positive genetic correlations of migraine with diastolic BP (DBP, r(g) = 0.11, P = 3.56 x 10(-06)) and systolic BP (SBP, r(g) = 0.06, P = 0.01), but not pulse pressure (PP, r(g) = -0.01, P = 0.75). Cross-trait meta-analysis reveals 14 shared loci (P <= 5 x 10(-08)), nine of which replicate (P < 0.05) in the UK Biobank. Five shared loci (ITGB5, SMG6, ADRA2B, ANKDD1B, and KIAA0040) are reinforced in gene-level analysis and highlight potential mechanisms involving vascular development, endothelial function and calcium homeostasis. Mendelian randomization reveals stronger instrumental estimates of DBP (OR [95% CI] = 1.20 [1.15-1.25]/10 mmHg; P = 5.57 x 10(-25)) on migraine than SBP (1.05 [1.03-1.07]/10 mmHg; P = 2.60 x 10(-07)) and a corresponding opposite effect for PP (0.92 [0.88-0.95]/10 mmHg; P = 3.65 x 10(-07)). These findings support a critical role of DBP in migraine susceptibility and shared biology underlying BP and migraine.